1967
DOI: 10.1111/j.1749-6632.1967.tb27701.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Studies of Human Leukemia*

Abstract: To determine whether viruses or mycoplasma have either an inductive or provocative effect on the pathogenesis of the human leukemia, it is first necessary t o isolate candidate agents. Next, the agents isolated must be characterized to determine whether they are known human viruses or mycoplasma. Finally, evidence must be accumulated to indicate whether the isolated agents can be implicated in the cause or pathogenesis of human leukemia. Although our long term studies' have provided a number of interesting fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1969
1969
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…The toxicity of M. fermentans is known (3,4), and most other species, even in high doses, are not toxic for mice (8). We confirmed this in our control series, but found marked toxicity in mice treated with pactamycin.…”
Section: Resultssupporting
confidence: 80%
“…The toxicity of M. fermentans is known (3,4), and most other species, even in high doses, are not toxic for mice (8). We confirmed this in our control series, but found marked toxicity in mice treated with pactamycin.…”
Section: Resultssupporting
confidence: 80%
“…The isolation of mycoplasma from human malignant tissues reported by some investigators and the effects on human chromosomes demonstrated here suggest the importance of further studies on the role of these microorganisms in certain carcinogenic processes (33)(34)(35).…”
Section: Discussionmentioning
confidence: 53%
“…Experimental inoculation of M fermentans induced leukemoid disease with myeloproliferative changes in mice. 12 However, the mycoplasmaoncogenesis hypothesis failed to advance because the same mycoplasma could also be found in nonleukemic children or adults though it was most frequently isolated from patients with leukemia. 13 Decades later, our understanding of disease process in chronic infections, cancer latency, and cancer-associated microbes has changed significantly.…”
Section: Introductionmentioning
confidence: 99%